Pathological Proximal Femoral Fracture in Mc-Cune Albright Syndrome: A Case Report (Global Journal of Medical Research, 2020)
A 25-year-old female present to us in the emergency department with atraumatic fracture of the proximal femur. She had a cafe-au-lait spot on the face and gave history of precocious puberty. A skeletal survey showed polyostotic fibrous dysplasia. A clinico-radiological diagnosis of McCune-Albright syndrome was made which was further confirmed on biopsy. An extra-medullary fixation was done and at 6 months follow-up, the fracture had united and the patient could walk without support.